Semi-automated delineation of breast cancer tumors and subsequent materialization using three-dimensional printing (rapid prototyping) - Schulz-Wendtland, Rüdiger; Harz, Markus; Meier-Meitinger, Martina; Brehm, Barbara; Wacker, Till; Hahn, Horst K.; Wagner, Florian; Wittenberg, Thomas; Beckmann, Matthias; Uder, Michael; Fasching, Peter; Emons, Julius (Journal of Surgical Oncology, 2017)
Three-dimensional (3D) printing has become widely available, and a few cases of its use in clinical practice have been described. The aim of this study was to explore facilities for the semi-automated delineation of breast cancer tumors and to assess the feasibility of 3D printing of breast cancer tumors.In a case series of five patients, different 3D imaging methods-magnetic resonance imaging (MRI), digital breast tomosynthesis (DBT), and 3D ultrasound-were used to capture 3D data for breast cancer tumors. The volumes of the breast tumors were calculated to assess the comparability of the breast tumor models, and the MRI information was used to render models on a commercially available 3D printer to materialize the tumors.The tumor volumes calculated from the different 3D methods appeared to be comparable. Tumor models with volumes between 325 mm(3) and 7,770 mm(3) were printed and compared with the models rendered from MRI. The materialization of the tumors reflected the computer models of them.3D printing (rapid prototyping) appears to be feasible. Scenarios for the clinical use of the technology might include presenting the model to the surgeon to provide a better understanding of the tumor's spatial characteristics in the breast, in order to improve decision-making in relation to neoadjuvant chemotherapy or surgical approaches. J. Surg. Oncol. 2017;115:238-242. © 2016 Wiley Periodicals, Inc.
EVALuna2:14618